Evaluation of HIV-Leishmania co-infection in patients from the northwestern Paraná State, Brazil - Élide Aparecida Oliveira (Acta Scientiarum. Health Sciences, 2011)
Leishmaniasis occurs throughout the world and is one of the opportunistic infections that attack HIV-infected individuals. Few data are available on American cutaneous leishmaniasis (ACL) in HIV-infected patients. Current research investigates the occurrence of HIV-Leishmania co-infection in HIV-infected individuals in an endemic region in Southern of Brazil. A non-randomized transversal investigation, molecular and serum epidemiologic type, on the occurrence of ACL in 169 HIV-infected patients was undertaken. The patients were followed up at the Integrated Nucleus of Health of the city Maringá, Southern of Brazil. Results showed that 13 (7.7%) of the HIV-infected patients also presented Leishmania (Viannia) DNA, detectable in blood by PCR. Serology, direct research, culture and PCR in skin material produced negative results. PCR positiveness for Leishmania was not associated with CD4 T lymphocytes count, opportunistic disease, treatment, use of proteases inhibitors, tattooing/piercing or use of injectable drugs, residential environment or previous ACL history. Results show that HIV- infected patients who live in endemic areas may reveal Leishmania DNA in the blood without any ACL symptoms. Above findings may be attributed to anti-retrovirus medicine that controls viral replication and maintains the functionality of the immune system and to a possible anti- Leishmania activity of these drugs.